2003
DOI: 10.1046/j.1440-1703.2003.00544.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term carbon budget of the above‐ground parts of a young hinoki cypress (Chamaecyparis obtusa) stand

Abstract: The carbon budget of the above‐ground parts of a young hinoki (Chamaecyparis obtusa) stand was analyzed over a 4‐year period to evaluate trends in changes in carbon use efficiency and growth conversion (biosynthetic) efficiency with stand development. Litter production of the stand was estimated from the stem cross‐sectional area at the crown base. A biomass increment was estimated using the stem volume of individual trees in the stand, measured at monthly intervals. Net production, estimated from litter produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
2
1
Order By: Relevance
“…In evergreen forest systems (eucalypts and other species), it is typically reported that leaf litter represents >50%, and often >70%, of total annual litterfall (Lamb 1985;O'Connell 1988;Pook et al 1997;Sundarapandian and Swamy 1999;Adu-bredu and Hagihara 2003). In our study however, leaf litter contributed only 23-34% of the total amount of litter.…”
Section: Discussioncontrasting
confidence: 73%
“…In evergreen forest systems (eucalypts and other species), it is typically reported that leaf litter represents >50%, and often >70%, of total annual litterfall (Lamb 1985;O'Connell 1988;Pook et al 1997;Sundarapandian and Swamy 1999;Adu-bredu and Hagihara 2003). In our study however, leaf litter contributed only 23-34% of the total amount of litter.…”
Section: Discussioncontrasting
confidence: 73%
“…Given the evidence for thermal acclimation of tissue-specific respiration rates to experimental warming in this experiment (Aspinwall et al, 2016;Drake et al, 2016b), we investigated growth and maintenance respiration as drivers of R a (McCree, 1970;Tjoelker et al, 1999;Amthor, 2000;Adu-Bredu & Hagihara, 2003). Separating growth and maintenance components of R a is not possible in all C-cycle studies, but we were able to couple direct measures of tree growth with continuous measurements of integrated whole-tree aboveground respiration to enable quantification of growth and maintenance components.…”
Section: Growth and Maintenance R Amentioning
confidence: 99%
“…The significant correlation between stem diameter and annual litterfall among the different tree species suggests that such correlation could be true in interspecific comparisons, at least among pioneer and early secondary tree species, as the intraspecific correlation observed by Adu-Bredu & Hagihara (2003). On the other hand, crown width seems to be as good predictor of litter production as stem diameter, in these early stages of succession.…”
Section: Litterfallmentioning
confidence: 73%